플로터를 이용한 슬로싱 충격하중 저감효과가 선체운동에 미치는 영향 - 남정우(Jung-Woo Nam); 김경성(Kyung-Sung Kim); 황성철(Sung-Chul Hwan); 허재경(Jae-Kyung Heo); 박종천(Jong-Chun Park); Moo-Hyun Kim (Han-guk haeyang gonghak hoeji (Online), 2012)
When a liquid cargo tank is partially filled with fluid, internal impact loads can be occurred from the vessel's motions. In this study, liquid sloshing problems with a thin top layer of particles with a lighter density than water and the coupling effects of the liquid-sloshing/vessel-motion were investigated in order to reduce the sloshing-induced impact loads. The PNU-MPS (Pusan-National-University-modified Moving Particle Simulation) method for solving the liquid motion inside a tank and the CHARM3D BEM (Boundary Element Method) based time-domain ship motion analysis program for vessel-motion simulation were coupled. From the simulation results, we could see that the floaters seemed to be quite effective at reducing the sloshing impact loads in the case of tank-only sloshing problems, but not as much for the coupling problem with vessel motion.